Submesoscale Eddy induced nitrate upwelling and effect on biological production in the upstream Kuroshio Current - Gloria Silvana Duran Gomez; Takeyoshi Nagai (Scientific Reports)
Abstract While the Kuroshio, a western boundary current in the North Pacific, transports a large amount of nutrients in dark subsurface layers, it remains elusive whether and how these subsurface nutrients are supplied to continental shelves along southern coast of Japan. Recent observations revealed that the upstream Kuroshio flowing through rough topography forms a large-scale turbulence hotspot that may supply nutrients to sunlit surface layers. However, the Kuroshio-Island interaction in this region may also induce eddies and nutrient upwelling which have neither been observed directly nor quantified. Here, through high-resolution in-situ observations, we show submesoscale ∼10 km nitrate structures along isopycnals, suggestive of eddy-induced upwelling. High-resolution simulations reproduce these features generated by submesoscale cyclonic eddy-induced nitrate upwelling at O(10) mmol N m−2 day−1, accounting ∼ 9% of net primary production in the area 400 km downstream during non-stratified season. Ecosystem model results suggest that rapid small zooplankton grazing could suppress the small phytoplankton increase, leaving a large fraction of supplied nitrate remain unused while it is carried by cyclonic eddies. These rather complex responses of lower trophic level ecosystem associated with submesoscale eddies in the upstream Kuroshio may partly explain how the Kuroshio sustains high biodiversity and biological production.